γ-crystallins of the chicken lens: remnants of an ancient vertebrate gene family in birds - Chen, Yingwei (FEBS J, 2016)
γ-Crystallins, abundant proteins of vertebrate lenses, were thought to be absent from birds. However, bird genomes contain well-conserved genes for γS and γN-crystallins. RTPCR detected spliced transcripts for both genes in chicken lens, with lower levels in cornea and retina/retinal pigment epithelium. The level of mRNA for γS in chicken lens was relatively very low even though the chicken crygs gene promoter had lens-preferred activity similar to that of mouse. Chicken γS was detected by a peptide antibody in lens, but not in other ocular tissues. Low levels of γS and γN proteins were detected in chicken lens by shotgun mass spectroscopy. Water soluble and insoluble lens fractions were analyzed and 1934 proteins (<1% false discovery rate) detected, increasing the known chicken lens proteome 30 -fold. Although chicken γS is well-conserved in protein sequence, it has one notable difference in leucine16, replacing a conserved surface glutamine in other γ-crystallins, possibly affecting solubility. However, L16 and engineered Q16 versions were both highly soluble and had indistinguishable circular dichroism, tryptophan fluorescence and heat stability(Tm values ~65C) profiles. L16 has been present in birds for over 100Myrand may have been adopted for a specific protein interaction in the bird lens. However, expression of all γ-crystallins in bird lenses has clearly been either eliminated or reduced during evolution. In view of this, the conservation of genes for γS and γN-crystallins in birds is surprising, suggesting they may have been preserved for some other role unrelated to the bulk properties of the lens.